2018
DOI: 10.1002/cam4.1858
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pretreatment concentration of plasma Epstein‐Barr virus DNA and tumor burden in nasopharyngeal carcinoma: An updated interpretation

Abstract: BackgroundPretreatment plasma Epstein‐Barr virus (EBV) DNA is an important tumor marker and prognostic factor in nasopharyngeal carcinoma (NPC). This study aimed to clarify the relationship between plasma EBV DNA level and tumor burden.Materials and MethodsPretreatment tumor burden was measured by radiologically delineated volumes, including nasopharynx tumor volume (GTVnx) and malignant nodes volume (GTVnd); pretreatment level of plasma EBV DNA was quantified by quantitative polymerase chain reaction. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
3
20
0
1
Order By: Relevance
“…Some studies have demonstrated that EBV status and primary tumor volume can be utilized in the prognostic stratification of NPC patients [48,49]. On the other hand, data confirming correlations between primary tumor volume and EBV-positivity is limited [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that EBV status and primary tumor volume can be utilized in the prognostic stratification of NPC patients [48,49]. On the other hand, data confirming correlations between primary tumor volume and EBV-positivity is limited [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the current study, we only found that EBV positive patients had more chance to have lower CD8% and higher NK%, no significant association of EBV positive with other peripheral immune parameters in advanced NPC was found. Previous studies reported that EBV DNA titers correlated with tumor burden, remission, and recurrence and could precede tumor development of NPC [32][33][34][35] . Thus, we further analyzed the association of the concentration of plasma EBV DNA with immune parameters.…”
Section: Discussionmentioning
confidence: 94%
“…However, our observations here in an actual screening scenario, suggest that serum EBV DNA performed more poorly in a setting where the disease identified is at a very early stage, as none of the NPC cases identified had levels >100 copies/ml. This may be because cell‐free EBV DNA is a reflection of tumor burden; the early‐stage NPC cases in our screen cohort had very limited disease and thus did not have significantly elevated levels. We also recognize that plasma‐based assays for cell‐free EBV DNA have a better sensitivity and specificity profile compared to serum‐based assays and our serum results here may not reflect the better accuracy profile reported in plasma‐based studies.…”
Section: Discussionmentioning
confidence: 99%